Pengembangan Sumber Daya Manusia Dalam Meningkatkan Kinerja Karyawan Pada Perum Bulog Kota Kendari - lasinggi, Kasmawati; jopang, jopang; Sitti Hairani Idrus3, Sitti Hairani Idrus (Business UHO: Jurnal Administrasi Bisnis, 2019)
The purpose of this study was to determine the role of human resource development in improving employee performance at the State Logistics Agency of Kendari City.The data collection techniques used in this study are field research in the form of direct interviews with informants as many as 6 people, then the data and information obtained from informants will be processed and analyzed descriptively qualitatively by reducing the data first, doing the data presentation and then pulling a general conclusion to answer the problem in research.Based on the description of the results of this study, it can be concluded that human resource development provides a fairly good assessment which means providing opportunities for employees to attend training, after education and training the employees are re-evaluated in order to ensure the progress of the individual is progressing. Education and training of employees will be able to deal with all changes in both the internal and external environment because it has been equipped with education and training. In general, BULOG employees agree that their employees' performance can be seen from their loyalty, work performance, honesty, work discipline, and responsibility for their work.